Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.5624/isd.2019.49.4.273
|View full text |Cite
|
Sign up to set email alerts
|

Effects of energy level, reconstruction kernel, and tube rotation time on Hounsfield units of hydroxyapatite in virtual monochromatic images obtained with dual-energy CT

Abstract: Purpose: This study was performed to investigate the effects of energy level, reconstruction kernel, and tube rotation time on Hounsfield unit (HU) values of hydroxyapatite (HA) in virtual monochromatic images (VMIs) obtained with dual-energy computed tomography (DECT) (Siemens Healthineers, Erlangen, Germany). Materials and Methods: A bone density calibration phantom with 3 HA inserts of different densities (CTWATER ® ; 0, 100, and 200 mg of HA/cm 3) was scanned using a twin-beam DECT scanner at 120 kVp with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…A study by Jang et al (2011) showed that the detection of small low-contrast lesions was improved as the kernel became smoother. The smooth kernel has been recommended for the assessment of abdominal soft tissue such as a liver lesion or tumor (Jeong et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…A study by Jang et al (2011) showed that the detection of small low-contrast lesions was improved as the kernel became smoother. The smooth kernel has been recommended for the assessment of abdominal soft tissue such as a liver lesion or tumor (Jeong et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The European Spine Phantom (No.145) contains 3 different inserts with trabecular bone compartments consisting of nominal design values of 50.2, 100.6, and 199.2 mg/cm3, which mimic the physiological range of BMD (13). A previous study showed that for reconstructed HA images of 0, 100, 200 mg/cm 3 , 120kVp, and 3 energy levels of 40, 70, and 140 keV, the mean HU value was within the range of 0-900 HU (41). The expected HU values of acrylic, LDPE, air, and Teflon were 120 HU, -100 HU, -1,000 HU, and 990 HU, respectively (14).…”
Section: Discussionmentioning
confidence: 99%